Cooperatives in the Upper Hungarian Region at the Intersection of Embourgeoisement and Nation-Building (1898–1918) - Gaučík, Štefan (Historical Studies on Central Europe, 2024)
Cooperatives, which abound in theoretical constructions, can be defined as associations of people who unite for a specific purpose and try to satisfy their economic needs through a democratically operated, jointly owned enterprise. However, it is an established fact that, by the end of the nineteenth century, industrial revolution and capitalism had brought many economic and social problems and manifold grave social challenges. This led to the further organizational development of self-help which, in turn, was an effective tool for shaping ethnic communities in the great trend of modernization and embourgeoisement. Self-help associations had a long tradition in the Habsburg Monarchy, including the territory of the Kingdom of Hungary, already from the first half of the nineteenth century. However, especially in the last third of the nineteenth century, the development and consolidation of cooperative networks in this Central European region went hand in hand with ethnically based cooperative self-organization controlled from above by the agrarian elites. Cooperative centres were established, which performed not only economic and social, but also national policy-related tasks, at the same time gradually monopolizing some producer-supplier areas. Certain interpretations view cooperatives as important tools of small-state economic nationalism, relegating their economic goals to the background. Focusing on the period between 1898 and 1918, this study deals with the process and stages of development in the Hungarian cooperative system in Upper Hungary, whose solid foundations were laid from the late nineteenth century onwards. Relying on archival sources, it discusses the strategies of the two most significant cooperative centres, the Országos Központi Hitelszövetkezet (National Central Credit Cooperative) and Hangya (’Ant’). In the early twentieth century, these Hungarian attempts at integration coincided with the increasingly pronounced decentralization ideas of the Slovak cooperative elite.